Two new Otoplanid species (Platyhelminthes: Rhabditophora: Proseriata) of the genera Orthoplana Steinböck, 1932 and Postbursoplana Ax, 1956 from the Tuscan coast (Italy) - Meini, Gianluca (Zootaxa, 2015)
Two new species of marine flatworms, collected on the sandy shores of Tuscany, are described. These species exhibit the morphological characteristics of the subfamilies Otoplaninae and Parotoplaninae (“Turbellaria”, Otoplanidae), but clearly differ from other described species. Orthoplana lunae sp. nov., is characterized by a body length of 1.4–1.6 mm, distinctive features of the testes and vitellaries, the male sclerotic apparatus composed of a median stylet (48–49 μm long), and 19 spines (17–44 μm long). Postbursoplana donoraticensis sp. nov., is characterized by a body length of 1.6–1.8 mm, the distribution of testes and vitellaries, the male sclerotic apparatus composed of 10 spines (46–70 μm). This new species has a greater body length relative to other species in this genus. They were collected along the sandy shores at low water mark at Partaccia (Marina di Massa, Ligurian Sea, Italy) and Marina di Donoratico (Livorno, Ligurian Sea, Italy), respectively.